Antiproliferative Imidazo-Pyrazole-Based Hydrogel: A Promising Approach for the Development of New Treatments for PLX-Resistant Melanoma - Silvana Alfei; Marco Milanese; Chiara Brullo; Giulia Elda Valenti; Cinzia Domenicotti; Eleonora Russo; Barbara Marengo (MDPI AG, 2023)
Aiming at developing a dermal formulation against melanoma, the synthesized imidazo-pyrazoles 2-phenyl-2,3-dihydro-1H-imidazo[1,2-b]pyrazole-7-carboxylic acid (3-methoxy-4-phenoxy-benzylidene)-hydrazide (4G) and 2-phenyl-2,3-dihydro-1H-imidazo[1,2-b]pyrazole-7-carboxylic acid (4-benzyloxy-3-methoxy-benzylidene)-hydrazide (4I) were screened on patient-isolated melanoma cells (MEOV NT) and on Vemurafenib (PLX4032)-resistant (MEOV PLX-R) ones. Since 4I on MEOV PLX-R cells was 1.4-fold more effective than PLX, a hydrogel formulation containing 4I (R4HG-4I) was prepared in parallel with an empty R4-based hydrogel (R4HG) using a synthesized antibacterial resin (R4) as gelling agent. Thanks to its high hydrophilicity, porosity (85%), and excellent swelling capability (552%), R4 allowed to achieve R4HG and R4HG-4I with high equilibrium degree of swelling (EDS) and equilibrium water content (EWC). Chemometric-assisted ATR-FTIR analyses confirmed the chemical structure of swollen and fully dried (R4HG-D and R4HG-4I-D) hydrogels. The morphology of R4HG-D and R4HG-4I-D was examined by optical microscopy and SEM, while UV-vis analyses were carried out to obtain the drug loading (DL%) and the encapsulation efficiency (EE%) of R4HG-4I. Potentiometric titrations were performed to determine the equivalents of NH3+ in both R4HG and R4HG-4I. The swelling and water release profiles of both materials and related kinetics were assessed by equilibrium swelling rate and water loss studies, respectively, while their biodegradability over time was assessed by in vitro degradation experiments determining their mass loss. Rheological experiments established that both R4HG and R4HG-4I are shear-thinning Bingham pseudoplastic fluids with low yield stress, thus assuring easy spreadability in a future topical application. Release studies evidenced a sustained and quantitative release of 4I governed mainly by diffusion. Upon favorable results from further experiments in a more realistic 3D model of melanoma, R4HG-4I could represent a starting point to develop new topical therapeutic options to adjuvate the treatments of melanoma cells also when resistant to currently available drugs.